2016
DOI: 10.1166/asl.2016.7761
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Guidance and Counseling Services Amongst Secondary School Teachers in Malaysia

Abstract: This study examined the effectiveness of guidance and counseling services in secondary schools by using Model Theory Context, Input, Process and Product (CIPP) developed by Stuflebeam (1960). The study used a survey design to examine the effectiveness of Guidance and Counselling services in schools. Theoretical Model CIPP by Stufflebeam used as a model study in view of the effectiveness of these services in secondary schools in Malaysia. A total number of 420 counseling teachers in secondary schools in the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several previous studies have emphasized the importance of Guidance and counseling in teachers to improve their professional quality and personality (Demir, 2015;Natesan, 2016;Wijaya, 2019). In line with the study, three treatments can be given to all three mental health profiles of teachers.…”
Section: Discussionmentioning
confidence: 63%
“…Several previous studies have emphasized the importance of Guidance and counseling in teachers to improve their professional quality and personality (Demir, 2015;Natesan, 2016;Wijaya, 2019). In line with the study, three treatments can be given to all three mental health profiles of teachers.…”
Section: Discussionmentioning
confidence: 63%
“…Most of the respondents here felt that, the available counseling services were not adequate enough to handle issues from students (Table 3 and Figure 3). A study carried out by Natesan et al (2016) in Malaysia found out that twothirds of the teachers counseling were classified as having a moderate effectiveness.…”
Section: Are the Teachers Involved In G And C Relieved From Some Of Their Teaching Duties?mentioning
confidence: 99%